A note on entanglement entropy and topological defects in symmetric orbifold CFTs - Michael Gutperle; Yan-Yan Li; Dikshant Rathore; Konstantinos Roumpedakis (Journal of High Energy Physics)
Abstract In this brief note we calculate the entanglement entropy in M ⊗N /S N symmetric orbifold CFTs in the presence of topological defects, which were recently constructed in [1, 2]. We consider both universal defects which realize Rep(S N ) non-invertible symmetry and non-universal defects. We calculate the sub-leading defect entropy/g-factor for defects at the boundary of the entangling surface as well as inside it.